1960
DOI: 10.4039/ent92801-11
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Predators of the Balsam Woolly Aphid, Adelges piceae (Ratz.) (Homoptera: Adelgidae) VIII. Syrphidae (Diptera),

Abstract: Several species of native syrphids have been found to prey upon the introduced balsam woolly aphid, Adelges piceae (Ratz.), in New Brunswick and three of these, Syrphus torvus O. S., Metasyrphus lapponicus (Zett.), and Neocnemodon coxalis (Curr.), are sometimes very common. As part of a long-term study of the biological control of the balsam woolly aphid by native and introduced predators, the life histories, natural control, population fluctuations and control value of these native syrphids have been investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

1962
1962
2016
2016

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…In our study, the two species of Eupeodes showed this behaviour and pupae were exclusively found on foliage of balsam fir trees. Brown and Clark (1960) also observed this behaviour for E. lapponicus on balsam fir trees infested by the balsam woolly adelgid. Differential niche selection is an important mechanism that permits species coexistence (Rosenzweig 1981; Berthiaume et al .…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…In our study, the two species of Eupeodes showed this behaviour and pupae were exclusively found on foliage of balsam fir trees. Brown and Clark (1960) also observed this behaviour for E. lapponicus on balsam fir trees infested by the balsam woolly adelgid. Differential niche selection is an important mechanism that permits species coexistence (Rosenzweig 1981; Berthiaume et al .…”
Section: Discussionmentioning
confidence: 64%
“…Larvae of D. venustus can feed on aphids, but these may not be their preferred prey (Vockeroth 1992). The three other species confirmed here as predators of balsam twig aphid are known as aphid predators (Vockeroth 1992), and larvae of S. torvus and E. lapponicus have been reared with aphids collected on balsam fir trees (Brown and Clark 1960; Vockeroth 1992).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations